Red-fleshed pitaya (Hylocereus polyrhizus) fruit colour and betacyanin content depend on maturity - Ding, Phebe; Chew, Mei Koi; Abdul Aziz, Suriani; Lai, Oi Ming; Abdullah, Janna Ong (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2009)
Red-fleshed pitaya fruit is a potential fruit for betacyanins extraction. However, there is lack of report on profiles and total contents of betacyanins in the peel and flesh. The objectives of this study were to determine colour, total betacyanins content and its separation in the peel and flesh of red-fleshed pitaya fruit harvested at 25, 30 and 35 days after flower anthesis (DAA) and to examine the usefulness of tristimulus colour measurement as predictors of pigment content in red-fleshed pitaya fruits. There were significant relationships between DAA and colour (L*, C* and h° values), and total betacyanins contents of peel and flesh of red-fleshed pitaya fruit. A total of three types betacyanins were separated from peel and flesh of pitaya fruit at 30 and 35 DAA while for 25 DAA, only one type of betacyanins was separated. The total concentration of betacyanins in the fruit peel of 25, 30 and 35 DAA was 0.24, 3.99 and 8.72 mg/mL, respectively. The fruit flesh contains 2.40, 7.93 and 11.70 mg/mL betacyanins at 25, 30 and 35 DAA, respectively, which was higher than peel. The tristimulus measurements can be adequately used to estimate the total betacyanins content of peel and flesh of red-fleshed pitaya fruit instead of tedious pigment extraction methods.